Preface to the Special Issue: The Impact of Ungulates and Other Mammalian Herbivores on Forest Ecosystems - Vodde, Floor; Köster, Kajar; Metslaid, Marek; Kuuluvainen, Timo (Finnish Environment Institute, 2016)
Peer reviewed